KESALAHAN PENULISAN ISTILAH ASING PADA PAPAN IKLAN ATAU REKLAME DI KOTA SEMARANG - Evi Chamalah, dan Aida Azizah, Meilan Arsanti, (Sasando, 2019)
This research was conducted to describe and explain the errors in writing foreign terms on billboards in Semarang city. The problem in this research was the form of error in writing foreign terms on billboards in Semarang city and its improvement. The research method that is used was descriptive qualitative. Sources of data in this study were curl boards or billboards in Semarangcity. The data included all of product document billboards whether the product or service advertisements in Semarang City. The data collection technique that is used was purposive sampling. The research instrument used by the researcher to retrieve data was the researcher herself.  In data retrieval, the researcher used a data card. Furthermore, the data were analyzed by examining the use of terms or foreign elements on billboards in the Semarang city that contained writing errors. After the data is collected, the researcher analyzed, classified, and evaluated / evaluated documents in the form of billboards. Based on research results from 11 billboards there were 19 foreign terms used. Thus, it could be concluded that the public considers the use of foreign terms more interesting and was expected to increase selling power. However, the used of foreign terms was not adjusted to the rules of language.